Anomalous intra diffusive behavior of chitosan/PVDF solid polymer electrolytes and the enhancement of effective specific capacitance with nanostructured spinel MnCoFeO4 electrode in solid-state supercapacitors. (20th July 2021) - Majumdar, Simantini; Ray, Ruma; Sen, Pintu
Highlights: Ionic conductivity increased by seven order in blended solid polymer electrolytes. Transport properties characterized by FTIR & impedance spectroscopy. Exploration of intra diffusive behavior of ions by fractional diffusion model. Evaluation of inter ionic transport properties of charge carriers in supercapacitor. Achievement of high effective specific capacitance 750 Fg −1 with MnCoFeO4 electrode. Abstract: Enhancement of conductivity in solid biopolymer electrolyte is an essential criterion for the fabrication of environment friendly solid-state supercapacitors. The conductivity of the blended polymer matrix composed of chitosan: PVDF (20: 80), salt LiClO4 (80 wt.%) and glycerol (15 wt.%) as plasticizer has increased by seven order in magnitude. The imaginary electric modulus ( M ″ ) is increased with increasing glycerol loading at higher frequency inferring a non-Debye type relaxation process. The anomalous intra diffusive behavior of the charge carriers inside the blended polymer matrix has been analyzed based on fractional diffusion model. Transport properties have also been studied from FTIR results. A hybrid solid-state supercapacitor has been developed with nano crystallites of manganese cobalt ferrite (MnCoFeO4 ) as electrode material and CS/PVDF blended polymer as solid state electrolyte. X-ray photoelectron spectroscopy (XPS) analysis of MnCoFeO4 reveals a partially inverse spinel structure with oxygen non-stoichiometry introduced by the mixed oxidation state of Mn ion. An unique model has been approached to evaluate inter ionic transport properties of the charge carriers in order to determine the effective specific capacitance of the electrode materials. A significant enhancement of effective specific capacitance of 750 Fg −1 has been achieved. Graphical abstract: Image, graphical abstract